Ethical issues when using social media for health outside professional relationships. (April 2015) - DeCamp, Matthew
Abstract Social media have the potential to revolutionize health and healthcare, but fulfilling this potential requires attention to the ethical issues social media may raise. This article reviews the major ethical issues arising when social media are used for research, public health, mobile health applications, and global health. It focuses on social media use outside fiduciary relationships between healthcare professionals and patients. Emphasis is given to the potential of social media in these contexts, the ethical issues relatively unique to each, and where possible how existing ethical principles and frameworks could help navigate these issues. In some cases social media create the circumstance for particular ethical issues but also facilitate managing them, such as in informed consent for research. In other cases, disagreement exists about whether social media – despite their potential – should be used for certain purposes, such as in public health surveillance (where confidentiality represents a significant ethical concern). In still others, ethical uncertainty exists about how social media will affect ethical issues, such as inequality in global health. As social media technologies continue to develop, identifying and managing the ethical issues they raise will be critical to their success in improving health while preserving fundamental ethical values.